Transient accumulation of 5-carboxylcytosine indicates involvement of active demethylation in lineage specification of neural stem cells - Wheldon, Lee M.; Abakir, Abdulkadir; Ferjentsik, Zoltan; Dudnakova, Tatiana; Strohbuecker, Stephanie; Christie, Denise; Dai, Nan; Guan, Shengxi; Foster, Jeremy M.; Corrêa, Ivan R; Loose, Matthew; Dixon, James E.; et al. (Elsevier, 2014)
5-Methylcytosine (5mC) is an epigenetic modification involved in regulation of gene activity during differentiation. Tet dioxygenases oxidize 5mC to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC). Both 5fC and 5caC can be excised from DNA by thymine-DNA glycosylase (TDG) followed by regeneration of unmodified cytosine via the base excision repair pathway. Despite evidence that this mechanism is operative in embryonic stem cells, the role of TDG-dependent demethylation in differentiation and development is currently unclear. Here, we demonstrate that widespread oxidation of 5hmC to 5caC occurs in postimplantation mouse embryos. We show that 5fC and 5caC are transiently accumulated during lineage specification of neural stem cells (NSCs) in culture and in vivo. Moreover, 5caC is enriched at the cell-type-specific promoters during differentiation of NSCs, and TDG knockdown leads to increased 5fC/5caC levels in differentiating NSCs. Our data suggest that active demethylation contributes to epigenetic reprogramming determining lineage specification in embryonic brain.